2014
DOI: 10.4236/cmb.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Biological Perspective of Cellular Stress-Directed Programmed Cell Death

Abstract: Each eukaryotic cell of multicellular organisms must be able to maintain its integrity by sensing both external and internal stimuli. The primary goal of the generated response mechanism is to drive back the system to the former or to a new homeostatic state. Moreover, the response has to provide an accurate survival-or-death decision to avoid any "misunderstanding" and its unwanted consequences. New data revealed that a systems-level crosstalk of molecular networks has an essential role in achieving the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…non-tolerable) ER stress levels were induced in the host cell ( Fig 2B and 2C ). Corresponding to our already published data [ 51 , 53 ], we further revealed here that cells survived with the help of autophagy-dependent self-degradation at low levels of ER stress, however, severe ER stress resulted in apoptotic cell death, meanwhile autophagy was switched off. According to previous experimental data [ 59 ], we confirm here that CQ/HCQ blocks the formation of autophagosomes, thereby disrupting autophagy-dependent survival even at low levels of ER stress.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…non-tolerable) ER stress levels were induced in the host cell ( Fig 2B and 2C ). Corresponding to our already published data [ 51 , 53 ], we further revealed here that cells survived with the help of autophagy-dependent self-degradation at low levels of ER stress, however, severe ER stress resulted in apoptotic cell death, meanwhile autophagy was switched off. According to previous experimental data [ 59 ], we confirm here that CQ/HCQ blocks the formation of autophagosomes, thereby disrupting autophagy-dependent survival even at low levels of ER stress.…”
Section: Discussionsupporting
confidence: 89%
“…Although the complexity of cellular systems makes this analysis highly challenging, a reductionist approach using a simple wiring diagram can be created containing the key components of the control network to address fundamental questions [ 47 , 49 ]. Accordingly, we have focused our research on the systems biology analysis of autophagy and its crosstalk with apoptosis with respect to ER stress [ 51 53 ]. Recently, we have shown by using both molecular and systems biology methods that autophagy always generates an evidently distinguishable threshold for apoptosis activation upon ER stress [ 51 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, excessive level of cellular stress results in an irreversible switch-like activation of apoptosis inducer and autophagy inducer gets inactive [ 35 ]. We suggested that the effect of crosstalk element and the double negative feedback loop between autophagy and apoptosis inducers have a crucial role in guaranteeing the proper decision-making between life and death [ 36 ]. Later Xu et al confirmed experimentally that autophagy induction in response to stress is uniformly unimodal, while apoptotic process gets activated in bimodal fashion [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive levels of autophagy can lead to apoptosis with increased stress levels [7, 1013]. Apoptosis, a kind of programmed cell death, can be triggered by the proapoptotic protein Bax, which causes mitochondrial membrane permeabilization to release mitochondrial cytochrome c into the cytoplasm, further activating Caspases to induce apoptosis [1417]. An increasing number of studies confirm that the autophagy and apoptosis networks are linked at various levels through common regulatory elements [18, 19].…”
Section: Introductionmentioning
confidence: 99%